VD_FINDINFO HC / 2023 / 624 vom 14. September 2023 - VD Tribunal cantonal (2023)
SUSPENSION DE LA PROCÉDURE, REJET DE LA DEMANDE, PRINCIPE DE LA CÉLÉRITÉ | 29 al. 1 Cst., 29 Cst., 126 al. 1 CPC (CH), 126 al. 2 CPC (CH), 126 CPC (CH), 319 let. b ch. 1 CPC (CH)